EDUCATIONAL SERVICES AS AN ECONOMIC INDICATOR: THE ROLE OF THE HUMAN FACTOR - Mansurova Muzaffarra Makhsudovna, (TADQIQOTLAR, 2026)
Abstract.  The  article  examines  the  importance  of  educational  services  as  a significant  economic  indicator  and  a  factor  in  the  formation  of  human  capital.  It substantiates that, under modern conditions, education should be considered not only as an  element of  the  social  sphere,  but  also  as  a  strategic  resource  for the  socio-economic development of the state. Special attention is paid to the role of the human factor in the system of educational services, including students’ motivation, teaching quality,  social  environment,  and  individual  characteristics.  Using  the  Republic  of Uzbekistan as an example, the article analyzes selected indicators of the development of the education sector, including education expenditure, literacy rate, the number of higher  education  institutions,  as  well  as  the  volume  and  dynamics  of  educational services. The article concludes that the effectiveness of educational services depends not only on quantitative indicators and the level of financing, but also on the ability of the education system to form high-quality human capital that meets the needs of the modern economy.